Histopathological abnormalities in the central arteries and veins of Fontan subjects - Hays, Brandon S; Baker, Michael; Laib, Annie; Tan, Wei; Udholm, Sebastian; Goldstein, Bryan H; Sanders, Stephen P; Opotowsky, Alexander R; Veldtman, Gruschen R (Heart (British Cardiac Society), 2018)
ObjectiveFontan circulations have obligatory venous hypertension, depressed cardiac output and abnormal arterial elastance. Ventriculovascular coupling is known to be abnormal, but the underlying mechanisms are poorly defined. We aim to describe the histopathological features of vascular remodelling encountered in the central arteries and veins in the Fontan circulation as a possible underlying pathological representation of abnormal ventriculovascular coupling.MethodsPostmortemvasculature (inferior vena cava (IVC), superior vena cava (SVC), pulmonary artery (PA), pulmonary vein (PV) and aorta) of 13 patients with a Fontan circulation (mean age 29.9 years, range 9.0–59.8 years) and 2 biventricular controls (ages 17.9 and 30.2 years) was examined.ResultsIVC and SVC: Eccentric and variable intimal fibromuscular proliferation occurred in 11 Fontan subjects. There was variable loss of medial smooth muscle bundles with reciprocal replacement with dense collagenous tissue.PA: Similar intimal fibromuscular proliferation was seen; however, these intimal changes were accompanied by medial thinning rather than expansion, medial myxoid degeneration and elastic alteration.PV: The PVs demonstrated intimal fibroproliferation and disorganisation of the muscular media.Aorta: The aortic lamina intima was thickened, with associated fibromuscular proliferation and elasticisation. There was also moderate lymphocytic inflammation in the aortic wall.ConclusionsVascular architectural remodelling is common in Fontan patients. The central veins demonstrate profound changes of eccentric intimal expansion and smooth muscle replacement with collagen. The pulmonary demonstrated abnormal intimal proliferation, and aortic remodelling was characterised by intima lamina thickening and a moderate degree of aortic wall inflammation.